High-energy density polymer current collector, preparation method and battery

By using conductive polymer current collectors containing active materials, the problems of weight reduction and production efficiency improvement of current collectors in lithium-ion batteries are solved, and the weight reduction and energy density of current collectors are achieved, while simplifying the process flow.

CN119905595APending Publication Date: 2025-04-29SHANDONG HERUN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311416796.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-29
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The current collector of existing lithium-ion battery has caused the increase in the frequency of interruptions during the battery manufacturing process during weight reduction, affecting production efficiency. At the same time, the traditional polymer composite foil process is complex and the equipment requirements are high.

Method used

The conductive polymer current collector containing the active material is used to form a high-strength and good conductivity current collector through the combination of a polymer matrix, a conductive agent, an active material, a flame retardant, an acid remover, a heavy metal ion complexing agent and a surface tension regulator.

Benefits of technology

The weight reduction and energy density of the current collector are achieved, while reducing the frequency of band breaks in the battery manufacturing process, improving production efficiency, and simplifying the process flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004524103990000051
    Figure BDA0004524103990000051
Patent Text Reader

Abstract

The invention discloses a polymer current collector for improving the energy density of a battery, a preparation method of the polymer current collector and the battery comprising the current collector. The current collector comprises a polymer matrix, a conductive agent, a deacidification agent, a flame retardant, a heavy metal particle complexing agent, a surface tension regulator and an active material. The polymer matrix provides required strength and ductility for the current collector. The conductive agent forms a conductive network in a polymer matrix to play a role in conducting electrons. Hydrofluoric acid and acidic substances generated in the system are removed by the acid removing agent in the system. The flame retardant is mainly used for preventing short-time combustion in the battery. The heavy metal ion complexing agent is mainly used for fixing metal ions dissolved out from positive and negative electrodes of the battery. And the surface tension regulator improves the spreading of the slurry on the pole piece. And the active material is dispersed in the polymer matrix, so that the energy density of the battery is improved, and capacity fading caused by loss of active lithium ions can be continuously supplemented in the circulation process. As the current collector adopts a polymer mode, compared with a metal current collector, the weight of the current collector can be obviously reduced, and the energy density of the battery is further improved. And meanwhile, the polymer current collector has fewer burrs in the battery cell manufacturing process, and no metal foreign matters are introduced, so that the overall cycle life and safety and reliability of the battery can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a current collector for improving the energy density of lithium ion batteries and a preparation method thereof. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in mobile phones, electric vehicles, electric buses and other fields. In addition, the penetration rate of lithium-ion batteries in electric ships, electric aircraft and energy storage fields has also continued to grow. This puts higher requirements on the energy density and power density of lithium-ion batteries. Generally speaking, the means to improve energy density is to increase the energy density of active materials, while reducing the proportion of inactive components, including current collectors and structural parts. The reduction of structural parts is mainly achieved through CTP and CTC technologies, that is, the battery cells cross the module and are directly grouped in the Pack or the chassis of the car. This further improves the energy density and volume density of the battery package. These technologies are also widely used by mainstream battery companies. In terms of weight reduction of current collectors, the technology currently used by various current collector manufacturers is to make the current collector as thin as possible, but the impact of thinning the current collector is the increase in the frequency of belt breakage during battery manufacturing, which will affect the improvement of production efficiency. Another technical route is polymer composite foil, which mainly vacuum evaporates a layer of metal on both surfaces of the polymer to achieve the purpose of weight reduction. This technical route is complex and requires the use of magnetron and evaporation processes, and has high requirements for equipment. Summary of the invention

[0003] In order to further solve the problem of reducing the weight of the current collector and improving production efficiency, the present invention uses a conductive polymer current collector containing active materials instead of a metal or composite metal current collector to achieve the purpose of reducing weight and providing partial energy density.

[0004] The conductive polymer current collector of the present invention is composed of a polymer matrix, a conductive agent, an active material, a flame retardant, an acid scavenger, a heavy metal ion complexing agent, a surface tension regulator and the like.

[0005] The polymer matrix includes a high-strength polymer and a lithium-ion-conducting polymer. The high-strength polymer includes but is not limited to polymers with high glass transition temperature or high crystallinity such as polyimide, polyurethane, polyethylene terephthalate, polypropylene, polyphenylene sulfide, polyetheretherketone, etc. The polymer has high tensile strength and elongation at break to ensure that the current collector does not break during the coating and rolling process of the lithium battery slurry, thereby ensuring the normal operation of production. The lithium-ion-conducting polymer includes polyethylene oxide, polyethylene oxide, polyacrylic acid, polyvinyl acetate, etc. These polymers form a homogeneous or microphase-separated bicontinuous phase with the high-strength polymer in the current collector. These molecular chains or microphase regions provide channels for the diffusion of lithium ions. Lithium ions can migrate in the current collector along the molecular chains or phase regions. This provides a path for the active material in the current collector to remove / insert lithium and the material exchange inside and outside the current collector. Due to the good compatibility between the polymers, a strong bonding force is formed between the binder in the positive and negative electrodes and the current collector. At the same time, the above-mentioned polymers can be a uniform or blended system, which can take into account both strength and flexibility. When using commonly used polymers such as polypropylene and polyethylene, the polymers can be cross-linked by irradiation or peroxide to improve the strength of the polymer and reduce the degree of creep of the polymer during use. Since a polymer current collector is used, the pole piece has good flexibility and can be well matched to the production and manufacturing processes of various types of batteries.

[0006] The conductive agent is distributed in the polymer matrix to form a conductive network, and the concentration of the conductive agent in the polymer is above the percolation concentration. The critical percolation concentration of conductive agents of different dimensions is related to their own aspect ratio. The mass ratio of the conductive agent to the polymer matrix is ​​0.001-50%. The conductive agent includes but is not limited to carbon black, carbon nanotubes, graphene, graphite, carbon fiber, etc. These conductive agents can be filled in the polymer matrix in one or more combinations to form a multi-level three-dimensional conductive network.

[0007] The active materials include, but are not limited to, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, Li2(NixCoyMn1-xy)O2, lithium oxalate, lithium nickel oxide, lithium manganate, lithium iron oxide, lithium oxalate, artificial graphite, natural graphite, silicon oxide, silicon oxide, lithium powder, etc. Among them, lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, Li2(NixCoyMn1-xy)O2, lithium oxalate, lithium nickel oxide, lithium manganate, etc. are used in the positive electrode current collector; artificial graphite, natural graphite, silicon oxide, silicon oxide, lithium powder, etc. are used in the preparation of the negative electrode current collector. The active materials contained in the positive electrode current collector will release part of the active lithium during the battery charging and discharging process to make up for the loss of active lithium during the cycle process; the active materials in the negative electrode can embed lithium during the charging process to provide part of the capacity. In particular, the lithium metal stored in the negative electrode current collector can also serve the purpose of supplementing the active lithium. Due to the presence of the polymer, it can be ensured that it is stably stored inside the current collector to avoid the reaction of moisture and oxygen. During long-term cycling, the negative electrode current collector containing lithium metal will slowly release some active lithium ions to compensate for the loss of active lithium. The proportion of active material added is 0-50%.

[0008] The flame retardant includes phosphate esters, fluorinated phosphate esters and phosphazene compounds. These substances are released from the current collector during the thermal runaway of the battery, inhibiting the combustion of the electrolyte and ensuring the safety of the battery itself. The flame retardant ratio ranges from 0.1-5%

[0009] The purpose of the acid scavenger is to capture acidic substances such as hydrofluoric acid generated in the electrolyte to avoid capacity decay caused by damage to the positive electrode material of the battery. These acidic substances are produced by the reaction of lithium salts in the electrolyte with water, and continue to corrode the positive electrode material during the cycle, causing irreversible battery capacity loss. The acid scavenger contained in the current collector can continuously absorb the generated hydrofluoric acid to a certain extent to protect the positive electrode material from corrosion and maintain the long-term stability of the battery. Acid scavengers include but are not limited to silicon dioxide, aluminum oxide, calcium oxide, etc. The proportion of acid scavengers ranges from 0.1-1%

[0010] The heavy metal ion complexing agent is used in conjunction with an acid scavenger. Due to the presence of acidic substances in the electrolyte, it will corrode the positive electrode material and produce free metal ions such as Ni, Co, Mn, Fe, etc. These ions may be deposited at the negative electrode, causing continuous damage to the SEI film and causing obvious battery degradation. In addition to the reaction between acidic substances and positive electrode materials, heavy metal ions are also introduced from raw materials and the manufacturing process. Therefore, the heavy metal ion complexing agent in the current collector can fix the generated heavy metal ions for a long time to reduce the harm caused by heavy metal ions. Including but not limited to EDTA, citric acid, aminoacetic acid, etc.

[0011] The surfactant regulator is selected according to the type of the polymer matrix. Due to the different types of polymer matrices, their surface tensions are also different. When the surface tension of the slurry is greatly different from the surface tension of the electrode, the slurry may experience shrinkage holes, foil leakage, and dimensional instability. The surfactant regulator can be filled in the current collector or coated on the surface of the current collector. The surfactant regulator filled in the current collector can migrate to the surface of the current collector to adjust the size of the surface tension. The surfactant regulator includes but is not limited to glycerol, polyacrylic acid, polyvinyl acetate, polyvinyl alcohol, polyol resin, carboxymethyl cellulose, etc.

[0012] The preparation method of the all-polymer current collector includes a variety of molding methods of polymer films, preferably solution casting, melt extrusion stretching, in-situ polymerization, etc. When a polymer current collector based on improving battery energy density is used in the positive electrode, it is called a polymer positive electrode current collector; when a polymer current collector based on improving battery energy density is used in the negative electrode, it is called a polymer negative electrode current collector. When preparing an all-polymer positive electrode current collector, the active material is selected from one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, Li2(NixCoyMn1-xy)O2, lithium oxalate, lithium nickel oxide, and lithium manganese oxide; when preparing a polymer negative electrode current collector, the active material is selected from one or more of artificial graphite, natural graphite, silicon oxide, silicon oxide, and lithium powder.

[0013] The solution method is to use a solvent to dissolve the polymer to form a polymer solution, and disperse the conductive agent, the active material, the acid scavenger, the flame retardant, the metal ion complexing agent and the surface tension regulator in the polymer solution to form a polymer composite solution. Finally, the polymer composite solution is cast into a polymer conductive film of a certain thickness. The polymer conductive film obtained can be stretched and shaped to obtain the polymer current collector. In order to further improve the strength of the current collector, the current collector can be irradiated or peroxide cross-linked. In order to further improve the affinity between the current collector surface and the lithium battery slurry, a layer of surface tension regulator with a thickness of about 1-2um can be coated on the surface of the current collector.

[0014] The melt extrusion stretching method is to add the granulated polymer, conductive agent, active material, acid scavenger, flame retardant, metal ion complexing agent and surface tension regulator into a twin-screw extruder for continuous mixing and extrusion, and pass the extruded composite through three rollers to form a polymer composite sheet of a certain thickness, and then after heating and biaxial stretching, form a current collector of the desired thickness. In order to further improve the strength of the current collector, the current collector can be cross-linked by peroxide or radiation. In order to further improve the affinity between the current collector surface and the lithium battery slurry, a layer of surface tension regulator with a thickness of about 1-2um can be coated on the surface of the current collector.

[0015] The in-situ polymerization method is to fully mix the polymer precursor with the conductive agent, the active material, the acid scavenger, the flame retardant, the metal ion complexing agent, etc., and form a polymer film of a certain thickness after casting, and then obtain a polymer composite film after high-temperature curing. After the polymer composite film is heated and biaxially stretched, a current collector of the desired thickness can be formed. In order to further improve the strength of the current collector, the current collector can be irradiated or peroxide cross-linked. In order to further improve the affinity between the current collector surface and the lithium battery slurry, a layer of surface tension regulator with a thickness of about 1-2um is coated on the surface of the current collector.

[0016] A wet electrode preparation process for a polymer current collector for improving battery energy density comprises the following steps: coating positive electrode slurry on both sides of the polymer positive electrode current collector by a commonly used extrusion or transfer coater, and obtaining positive electrode sheets after drying, winding, rolling and slitting; and coating positive electrode slurry on both sides of the polymer negative electrode current collector by a commonly used extrusion or transfer coater, and obtaining negative electrode sheets after drying, winding, rolling and slitting.

[0017] A dry electrode preparation process comprising a polymer current collector for improving battery energy density comprises the following steps: dry-mixing and rolling a positive electrode active material, a conductive agent and a binder to form a self-supporting film, and then thermally bonding the polymer positive electrode current collector to the obtained self-supporting film, and then winding and slitting to obtain a positive electrode sheet; dry-mixing and rolling a negative electrode active material, a conductive agent and a binder to form a self-supporting film, and then thermally bonding the polymer negative electrode current collector to the obtained self-supporting film, and then winding and slitting to obtain a negative electrode sheet.

[0018] The manufacturing process of a battery including a polymer current collector for improving battery energy density includes: winding the obtained positive electrode sheet, the obtained negative electrode sheet and the separator to obtain a wound electrode core; cutting the obtained positive electrode sheet into a pole ear, and cutting the obtained negative electrode sheet into a pole ear. After stacking the two pole sheets and the separator, a laminated pole core can be obtained. The polymer pole ear is welded to the battery pole column or metal pole ear by a heat sealing machine, and after casing, liquid injection and chemical separation, a battery including a polymer current collector for improving battery energy density can be obtained. DETAILED DESCRIPTION

[0019] In order to further illustrate the present invention, the present invention will be described in further detail in conjunction with specific embodiments.

[0020] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art can think of other obvious variations. The basic principles of the present invention defined in the following description can be applied to other embodiments, variations, improvements, equivalents, and other technical solutions that do not deviate from the spirit and scope of the present invention.

[0021] Example 1: PET is dissolved in NMP to form a PET solution, and 10% SUPER P Li and 5% CNT, 10% lithium nickelate, 1% silicon dioxide, 1% trimethyl phosphate, 1% polyacrylic acid, etc. are dispersed in the polymer solution to form a polymer composite solution. The above polymer composite solution is cast into a polymer conductive film with a thickness of 20um. The obtained polymer conductive film is subjected to biaxial stretching and shaping at 130-150°C to obtain a 12um polymer current collector. In order to further improve the strength of the current collector, the current collector can be cross-linked by radiation. In order to further improve the affinity between the current collector surface and the lithium battery slurry, a layer of surface tension regulator with a thickness of about 1um is coated on the surface of the current collector. That is, a polymer positive electrode current collector can be obtained.

[0022] The preparation process of the battery containing the above-mentioned polymer positive electrode current collector is as follows:

[0023] (1) LFP:Super P Li:PVDF was mixed in a double planetary mixer at a ratio of 92:5:3 to prepare a positive electrode slurry with a solid content of 55%.

[0024] (2) coating the positive electrode slurry on both sides of the all-polymer positive electrode current collector by an extrusion coating machine, and obtaining the positive electrode sheet after drying, winding and slitting;

[0025] (3) Using an extrusion coater to coat the negative electrode slurry on both sides of a commonly used copper current collector, and after drying, winding, and slitting, the negative electrode sheet can be obtained;

[0026] (4) Winding the positive electrode sheet obtained in (1), the negative electrode sheet obtained in (2), and the separator to obtain a wound electrode core;

[0027] Cut the tabs of the positive electrode sheet obtained in (1), cut the tabs of the negative electrode sheet obtained in (2), and stack the separator to obtain a laminated electrode core;

[0028] (5) A battery having a polymer current collector with improved energy density can be obtained by welding the tabs to the battery poles using a heat sealer, and then putting on a shell, injecting liquid, and forming a component.

[0029] The difference between Comparative Example 1 and Example 1 is that the positive electrode current collector is made of conventional aluminum foil with a thickness of 13 μm. The electrode tab welding method is ultrasonic welding.

[0030] As can be seen from the table below, compared with Comparative Example 1, due to the use of a polymer current collector, the energy density of the battery cell in Example 1 is increased by about 7%, the 45-degree cycle performance is increased by 2.3%, and the 60-degree storage performance is increased by 1.6%. This shows that using the polymer current collector prepared by the present invention instead of the metal current collector can significantly increase the battery energy density and extend the battery life.

[0031]

Claims

1. The present invention discloses a polymer current collector for improving battery energy density, a preparation method thereof and a battery comprising the current collector. The current collector comprises a polymer matrix, a conductive agent, an acid scavenger, an active material, a flame retardant, a heavy metal particle complexing agent and a surface tension regulator. The polymer matrix provides the strength and ductility required for the current collector. The conductive agent forms a conductive network in the current collector to conduct electrons. The acid scavenger removes hydrofluoric acid and acidic substances generated in the system to avoid corrosion to the positive electrode material. The active material can provide partial capacity to improve the energy density of the battery; at the same time, it can continuously supplement the capacity attenuation caused by the loss of active lithium ions during the cycle process. The flame retardant mainly inhibits short combustion in the battery. The heavy metal ion complexing agent mainly captures the metal ions dissolved from the positive and negative electrodes of the battery to prevent the battery from self-discharging caused by the deposition of metal ions. The surface tension regulator mainly improves the surface tension difference between the foil and the positive and negative electrode slurry of the battery, and improves the spreading of the battery slurry on the pole piece.

2. The polymer matrix of claim 1 includes, but is not limited to, engineering plastics such as polyimide, polyurethane, polyethylene terephthalate, polypropylene, polyphenylene sulfide, polyetheretherketone, etc. The polymer matrix is ​​one or a combination of several thereof.

3. The conductive agent of claim 1 includes but is not limited to copper powder, aluminum powder, carbon black, multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, graphite, vapor-phase carbon fiber, carbon fiber, etc. The conductive agent is one or a combination of several thereof.

4. The active material described in claim 1 includes but is not limited to lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, Li2(NixCoyMn1-xy)O2, lithium oxalate, lithium nickel oxide, lithium manganese oxide, and lithium ferrite in the positive electrode current collector; and includes but is not limited to artificial graphite, natural graphite, silicon oxide, silicon dioxide, etc. in the negative electrode current collector.

5. The flame retardant of claim 1 includes but is not limited to one or more combinations of phosphates, fluorinated phosphates and phosphazenes.

6. The purpose of the acid scavenger described in claim 1 is to capture acidic substances such as hydrofluoric acid generated in the electrolyte to avoid capacity decay caused by damage to the positive electrode material of the battery. The acid scavenger includes but is not limited to a combination of one or more of silicon dioxide, aluminum oxide, calcium oxide, etc.

7. The current collector preparation method described in claim 1 includes common processing methods for polymer films such as solution casting, melt extrusion stretching, and in-situ polymerization.

8. According to claim 1, the polymer matrix ratio ranges from 50-80%, the conductive agent ratio ranges from 0.001-50%, the flame retardant ratio ranges from 0.1-5%, the acid scavenger ratio ranges from 0.1-1%, and the active material ratio ranges from 0-50%.

9. The polymer current collector according to claim 1 has a thickness of 1-50 um.

10. A pole piece, characterized in that: Comprising the polymer current collector as claimed in any one of claims 1 to 9.

11. A lithium battery, characterized in that: Comprising a pole piece as claimed in claim 10.